Properties of medium density fiberboard from rubberwood and leucaena in relation to wood ratio and resin content / Nur Othman Suratman ...[et al.] - Suratman, Nur Othman; Wan Abdul Rahman, Wan Mohd Nazri; Mohd Yunus, Nor Yuziah; Razali, Nur Amalina (2015)
This study used Leucaena and rubberwood species as the raw materials in the manufacture of medium density fiberboard (MDF). The objective were to determine the physical and mechanical properties of MDF using Leucaena and rubberwood and evaluate the effect of different wood ratios and resin content on board properties. Urea formaldehyde (UF) was used as a binder and target board density was 700 kg/m3. Medium density fiberboard was assessed for the mechanical (bending and internal bonding) and physical (thickness swelling) properties according to European Standard (EN 622-5:2006). Mechanical properties revealed the highest MOR value of 15.09 MPa with resin content of 12% from wood ratios of 80% Rubberwood and 20% Leucaena. However, the highest result for MOE is 2005 MPa and IB is 0.7 MPa obtained from wood ratios of 20% Rubberwood and 80% Leucaena with 12% resin content. For the physical properties wood ratio with 80% Rubberwood and 20% Leucaena and 12% resin content had the best TS value with 21.59%. The results revealed that wood ratio and resin contents shows significant effect on board mechanical properties of MOR, MOE and TS values. However, IB values shows no not significant effect for wood ratio combination.